2022
DOI: 10.29173/aar141
|View full text |Cite
|
Sign up to set email alerts
|

Canadian School Administrators' Statistical Reasoning about Probability, Effect, and Representativeness

Abstract: How do Canadian school leaders interpret data to inform their decisions? How do they reason with probability concepts? These are the questions we are investigating in the first year of this longitudinal bilingual project conducted in Alberta, British Columbia, and Ontario. Our theoretical framework is inspired by the semiotic perspective of Charles Sanders Peirce (1839-1914) which suggests that interpretation is a triadic process integrated in a social context that puts in relation a sign, an object, and an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The findings of a 11 year research project with Principal Investigator Taysum revealed a professional challenge for policy makers, experienced teachers and diverse communities today is i) these groups do not have a clear working definition of epistemology, ii) they do not understand why synthesising epistemologies is important to create robust evidence bases to democratise knowledge; iii) they do not understand whose epistemology counts in research that generates Models of Effective and Efficient Measures for education and training pathways to democracy or democracy's anti-thesis of dictatorship and iv) they have not been prepared to synthesise epistemologies to build robust evidence bases to develop culturally relevant models of effectiveness that map to models of effectiveness Taysum, 2012aTaysum, , 2014Taysum, , 2017Taysum, Arar, Chopra, Imam, Harrison, McNamara, O'Hara et al, 2020). Hunter (2022) documents that educational leaders in Canada were not able to analyse quantitative data, and they were analysing qualitative data 6 months into a programme of study that does not give the opportunity to implement back dated interventions. Rather teachers need to be empowered to do their own research in the classroom to identify when measures on pathways to culturally relevant education outcomes have not been met and need to be mitigated for through assessment for social and personal learning.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of a 11 year research project with Principal Investigator Taysum revealed a professional challenge for policy makers, experienced teachers and diverse communities today is i) these groups do not have a clear working definition of epistemology, ii) they do not understand why synthesising epistemologies is important to create robust evidence bases to democratise knowledge; iii) they do not understand whose epistemology counts in research that generates Models of Effective and Efficient Measures for education and training pathways to democracy or democracy's anti-thesis of dictatorship and iv) they have not been prepared to synthesise epistemologies to build robust evidence bases to develop culturally relevant models of effectiveness that map to models of effectiveness Taysum, 2012aTaysum, , 2014Taysum, , 2017Taysum, Arar, Chopra, Imam, Harrison, McNamara, O'Hara et al, 2020). Hunter (2022) documents that educational leaders in Canada were not able to analyse quantitative data, and they were analysing qualitative data 6 months into a programme of study that does not give the opportunity to implement back dated interventions. Rather teachers need to be empowered to do their own research in the classroom to identify when measures on pathways to culturally relevant education outcomes have not been met and need to be mitigated for through assessment for social and personal learning.…”
Section: Introductionmentioning
confidence: 99%